Employer’s Perception Towards Acceptance of Disabled Workers in Food Service - Roddin, Rohayu; Kasim, Nurul Aizam Sazween (Research and Innovation in Technical and Vocational Education and Training, 2021)
This study was conducted on employers in the food service industry in Johor Bharu district. The purpose of this study was to explore employers’ perceptions of the acceptability of workers with disabilities people (OKU). This study also determines the acceptance factors and factors of employer rejection of disabilities people (OKU) in the field of food service. This study uses a qualitative approach through a semi-structured interview method. Data analysis using the thematic analysis method is broken down into themes. The findings show that employers’ perceptions of accepting workers from the disabled in the food service field are wide open and allow disabled people to work in accordance with the same skills and competencies as other (normal) workers. It is hoped that this study will provide positive perceptions to employers and other employees of the disabled and can help increase the confidence and morale of the disabled to continue to work and not be afraid to venture into the field of interest as employers are more open to accepting anyone even from the disabled with the skills, and ability to do a job.